New insights into resistance of Helicobacter pylori against third‐ and fourth‐generation fluoroquinolones: A molecular docking study of prevalent GyrA mutations. Issue 5 (7th July 2019) - Salehi, Najmeh; Attaran, Bahareh; Eskini, Negin; Esmaeili, Maryam; Sharifirad, Atefeh; Sadeghi, Mehdi; Mohammadi, Marjan
Abstract: Background: Fluoroquinolones hinder bacterial DNA replication by inhibiting DNA gyrase. However, mutations, in the QRDR segment of its A subunit (GyrA), cause antibiotic resistance. Here, the interactions of levofloxacin (LVX), gemifloxacin (GXN), and moxifloxacin (MXN) with Helicobacter pylori GyrA, in LVX‐resistant vs ‐sensitive strains, were studied. Methods: Levoflixacin‐sensitive (n = 4) and ‐resistant (n = 9) H pylori strains, randomly selected from another antibiotic susceptibility study, underwent PCR amplification of gyrA gene, spanning the QRDR segment. The amplified gene fragments were sequenced and aligned. The homology model of H pylori GyrA was built based on that of Escherichia coli, and energy minimization was done. The interaction patterns of LVX, GXN, and MXN with GyrA were analyzed via molecular docking studies. Results: Sequence alignment of the 13 studied strains, created 5 categories of strains: (A) wild type‐like ( H pylori ATCC26695), (B) N87K‐only, (C) D91N‐only, (D) N87K + V94L, and (E) D91N + A97V mutations. The minimum inhibitory concentrations (MIC) for LVX‐sensitive (category A) and ‐resistant (categories B‐E) strains were <1 mg/L and ≥32 mg/L, respectively. The binding mode of GyrA in category A with LVX identified G35/N87/Y90/D91/V94/G114/S115/I116/D117/G118/D119, as key residues, some residing outside the QRDR segment. Category B strains lost only one interaction (G35), which led to elevated binding free energy (∆G) and full LVX resistance. Categories C‐E lost more contacts, with higher ∆G and again full LVX resistance. GXN bound to GyrA of categories A and B via a different set of key residues, while MXN retained the lost contact (G35) in LVX‐resistant, category B strains. Conclusion: Using molecular docking tools, we identified the key residues responsible for interaction of GyrA with LVX, GXN, and MXN. In the presence of N87K‐only mutation, the loss of one of these contacts (ie, G35) led to full LVX resistance. Yet, GXN and MXN overcame this mutation, by retaining all key contacts with GyrA.